The Effect Of Aeration Rate On The Growth Of Blue Green Microalgae in Buffalo Dung As Alternative Media - EDWIN YONATHAN GURNING GURNING; AMOS IMANUEL; NINA JULIANA ROBERTA TURNIP; ADELINA MANURUNG (Microbiology Indonesia, 2019)
The high demand of Arthrospiraplatensis as a veritable protein source encourages its mass production worldwide. Currently, mass production of Arthrospiraplatensis is hindered by the relatively high price of the growth media. Recently, it is discovered that Arthrospiraplatensis can be cultivated using buffalo dung as an alternative medium. Buffalo dung is an excellent source of nitrogen and phosphorus which are principal macronutrients for the growth of Arthospiraplatensis. In addition to nitrogen and phosphorus, carbon is also a macronutrient that is important to the growth of microalgae. The carbon source used by the microalgae is carbon dioxide, which is consumed through photosynthesis. Carbon dioxide can be derived directly from the atmosphere as atmospheric CO2 existing as much as 0.04%-v/v in air, which can be provided directly using an aeration pump into the growth medium microalgae. During the aeration process, CO2 mass transfer occurs from the gaseous phase into the liquid phase. This research aims to investigate the effect of the aeration rate on the growth of the blue-green microalgae Arthrospiraplatensisusing buffalo dung media as an alternative medium. Arthrospiraplatensis will be cultivated on buffalo dung media using various aeration rates to determine the effect of aeration on the specific growth rate (µ). The air will also be pumped into the growth medium without Arthrospiraplatensis at the specific aeration rates to determine the mass transfer coefficient (kLa) that occurs from the air leading to growth medium. Analysis of mass transfer coefficient (kLa) of carbon dioxide will be conducted using the sulfite method. Variation of aeration that used in this research are 0.2 vvm; 0.4 vvm; 0.6 vvm; 1.2 vvm; 2.4 vvm that has mass transfer coefficient dan specific growth rate are 0.005 min-1 and 0.1987 day-1; 0.009 min-1 and 0.2279 day-1; 0.012 min-1 and 0.2044 day-1; 0.034 min-1 and 0.1918 day-1; 0.035 min-1 and µ in 2.4 vvm can’t determine, respectively.